Point-to-point multilayer antenna design for gain and bandwidth improvement for ism 5.8 GHz - Nafea, Safa Nassr (2016)
In this research, a compact multilayer antenna was proposed to enhance the gain and operating bandwidth of a single layer patch antenna and reduce the side lobe level (SLL). The proposed multilayer antenna consists of a feeding patch and three dielectric superstrate layers located at a specific height for each layer above the ground plane to enhance the performance of the antenna over the Industrial, Scientific, and Medical ISM band (5.725 - 5.875) GHz. Based on literature review and theoretical analysis, adding superstrate layers above the patch antenna to enhance the performance of the antenna is presented in this thesis. The objectives of this thesis include enhancing the gain of the antenna over the ISM band and reducing the SLL using multilayer antenna, which is composed of patch antenna covered by layers of dielectric material. The feeding patch was designed based on theoretical analysis of designing a patch antenna with optimization to achieve an operating frequency of 5.8 GHz. This feeding patch is composed of an optimized rectangular patch with four circles located at corners of the patch to obtain higher gain. However, three slots etched from the surface of the patch to improve the operating bandwidth. The feeding patch was printed on Rogers RT / Duroid 5880 substrate which has dimensions of, while the ground plane of the antenna which is under then antenna's substrate directly has the same length and width of the substrate with thickness of 17 which is the same thickness of the laminated patch's copper. The feeding patch resonated at 5.806 GHz with operating bandwidth of 130.15 MHz and gain of 8.23 dB with 88.98 % radiation efficiency and radiation pattern which has -4 dB SLL and 70.5o Half Power Beam Width (HPBW). For enhancing the performance of the antenna, three multilayer antenna designs (Antenna 1, Antenna 2, and Antenna 3) were presented and simulated. The performance of each antenna was studied. A comparison between the performance of these antennas has been taken in consideration to achieve the optimum performance among these multilayer antennas. The first multilayer antenna design (Antenna 1) utilized three FR4 layers located above the feeding patch at specific height for each layer. The FR4 superstrate layers have dielectric constant ( ) of 4.3 and loss tangent ( ) of 0.02, while the dimensions of each layer are . The area of each superstrate layer used in Antenna1 is the same area of the feeding patch. Antenna 1 had resonated at 5.8 GHz. The gain and operating bandwidth were 10.78 dB and 183.29 MHz, respectively, with 48o HPBW and low SLL radiation pattern. The second multilayer antenna design (Antenna 2) is composed of feeding patch and three Rogers RO3010 layers located above the feeding patch at specific height for each layer. The Rogers superstrate layers have dielectric constant ( ) of 10.2 and loss tangent ( ) of 0.0023, while the dimensions of each layer are . Antenna 2 resonated at 5.8 GHz and provided gain and operating bandwidth of 11.30 dB and 190.54 MHz, respectively, 46.4o HPBW and low SLL radiation pattern The third multilayer antenna design (Antenna 3) utilized three Rogers RO3006 as superstrate layers. These superstrate layers have dimensions of for each layer, which show larger area than the area of the feeding patch. Antenna 3 had resonated at 5.806 GHz and achieved gain and operating bandwidth of 11.70 dB and 189.39 MHz, respectively. Antenna 3 has a lower SLL radiation pattern than those achieved for Antenna 1, Antenna 2, where the side lobe level and HPBW for Antenna 3 found to be -14.9 dB and 43.1o, respectively. Antenna 3 proposed gain and bandwidth improvement with SLL reduction and HPBW narrowing where 3.5 dB gain enhancement and bandwidth improvement around 60 MHz with SLL reduction around -11 dB are achieved compared to the single layer feeding patch. Antenna 3, which shows the optimum simulated results compared to the performance of other antennas (Antenna 1 and 2), has been fabricated. The superstrate layers are located above the feeding patch at specific height for each one, according to the optimum heights which were optimized in simulation and were fixed using nylon spacers. The measurements of the return loss and the gain of the fabricated antenna are obtained. A slight difference was observed between the simulated and measured results due to the occurrence of deficiencies and analogue losses through fabrication process, which were not considered in the simulator environment. Compared to the multilayer antennas presented in literature review in this thesis, the proposed antenna has a reduced size of 76.34% and low SLL of -14.9 dB due to optimizing the height of superstrate layers. Moreover the multilayer proposed antenna achieved lower return loss by 217%, while multilayer antenna presented in literature review overcome the proposed antenna by 9.4% for gain. The SLL of antenna's radiation for Antenna 1, Antenna 2, and Antenna 3 were eliminated due to optimizing the height of each superstrate layer. By using the multiple superstrate layers, the gain was enhanced, the operating bandwidth was improved, and the radiation efficiency of the antenna was increased while the return loss and the SLL were decreased. The proposed point-to-point multilayer antenna in this research (Antenna 3) is a directive antenna with gain suitable for Line of Sight (LOS) links that operating at 5.8 GHz.